Aqueous IR Bagendit rice leaf extract decreases reticulocyte count in lead-exposed rats - Santosa, Budi; Sunoko, Henna Ria; Sukeksi, Andri (Universa Medicina, 2018)
BACKGROUNDLead acetate may inhibit the enzyme aminolevulinate dehydratase (ALAD) resulting in decreased heme synthesis (and consequently in anemia) but in increased number of reticulocyte cells. IR Bagendit paddy leaf water extract has a high metallothionein protein content which acts to bind to lead. The study objective was to determine whether aqueous IR Bagendit rice leaf extract dosage variations prior to lead exposure decreases reticulocyte count in lead-exposed rats. METHODSThe study was of randomized post test only control-group design involving a sample of 28 rats, that were randomized into 4 groups consisting of 1 control group and 3 treatment groups, daily administered with aqueous IR Bagendit rice leaf extract of respectively 0.2; 0.4; 0.8 mg using a feeding tube up to week 13. Lead exposure was also given using a feeding tube to both control and treatment groups at a dose of 0.5 g/kg BW/day, up to week 13. The reticulocyte count was then examined using supravital brilliant cresyl blue staining. The reticulocyte count was determined per 1000 erythrocytes and then converted into a percentage. Kruskal Wallis test followed with Bonferroni test was conducted to figure out the differences between groups. RESULTSMean reticulocyte count decreased significantly, starting from the control group up to the third treatment group (15.48 ± 3.41; 12.25 ± 03.28; 10.45 ±1.47; 9.10 ± 2.35 average per unit) (p=0.02). The Bonferroni test showed that the reticulocyte count was significantly decreased in the third treatment group (p=0.004). CONCLUSIONAqueous rice leaf extract significantly decreases reticulocytes in rats exposed to lead.